Mutations within the S4–S5 Linker Alter Voltage Sensor Constraints in hERG K(+) Channels - Van Slyke, Aaron C. (The Biophysical Society, 2010)
Human ether-a-go-go related gene (hERG) channel gating is associated with slow activation, yet the mechanistic basis for this is unclear. Here, we examine the effects of mutation of a unique glycine residue (G546) in the S4–S5 linker on voltage sensor movement and its coupling to pore gating. Substitution of G546 with residues possessing different physicochemical properties shifted activation gating by ∼−50 mV (with the exception of G546C). With the activation shift taken into account, the time constant of activation was also accelerated, suggesting a stabilization of the closed state by ∼1.6–4.3 kcal/mol (the energy equivalent of one to two hydrogen bonds). Predictions of the α-helical content of the S4–S5 linker suggest that the presence of G546 in wild-type hERG provides flexibility to the helix. Deactivation gating was affected differentially by the G546 substitutions. G546V induced a pronounced slow component of closing that was voltage-independent. Fluorescence measurements of voltage sensor movement in G546V revealed a slow component of voltage sensor return that was uncoupled from charge movement, suggesting a direct effect of the mutation on voltage sensor movement. These data suggest that G546 plays a critical role in channel gating and that hERG channel closing involves at least two independently modifiable reconfigurations of the voltage sensor.